Flipped classroom integration in food technology to enhance constructive aspect of learning - Shukri, Radhiah; Zainal Abedin, Nur Hanani (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
Flipped classroom is promoted as a good platform to initiate new learning process. The innovations include gamification in the class such as cross word puzzle, know your identity, mix and match, etc. These games can be conducted in groups or individual, as a part of the assessment or class activities. Being one of the tools in flipped classroom approach, video lectures are given to the students before class to watch and digest it. The videos are self-paced and will empower students by giving them choice to access it anywhere, anytime based on their convenience. Beside that, motivation elements and e-learning tools are vastly introduced in learning environment.